Biomass Waste Incorporation in La0.6Sr0.4Co0.2Fe0.8O3-α˗Ba(Ce0.6Zr0.4)0.9Y0.1O3-δ Composite Cathode: Effects on Microstructural and Physical Properties - Ismail, Ismariza; Abdullah, Nur Ashafieka; Karim, Norizah Abd; Johari, Shazlina; Ramli, Muhammad Mahyiddin (Universitas Gadjah Mada, 2025)
This study explores the incorporation of rice straw as a pore-forming agent in fabricating the La0.6Sr0.4Co0.2Fe0.8O3-α˗Ba(Ce0.6Zr0.4)0.9Y0.1O3–δ (LSCF-BCZY) composite cathode, focusing on its microstructural and physical properties. Conventional cathode materials often face challenges in balancing porosity and structural stability, with synthetic pore formers posing environmental and consistency concerns. To address these issues, rice straw was introduced into the cathode matrix at varying weight percentages, and the composites were sintered at 1000 °C. The addition of rice straw was evaluated using X-ray diffraction, scanning electron microscopy, and densitometry. The results revealed that increasing rice straw content significantly enhanced cathode porosity, rising from 5.53 to 27.74%, with a concomitant reduction in density from 1.33 to 0.93 g/cm3, while maintaining the crystalline stability of the LSCF-BCZY composite. Enhanced porosity suggests improved reactant diffusion to active sites, potentially benefiting the cell's performance in future energy applications. This work highlights the potential of agricultural waste as a sustainable and effective alternative to synthetic pore formers in cathode fabrication.